2023
DOI: 10.1111/mcn.13485
|View full text |Cite
|
Sign up to set email alerts
|

High consumption of unhealthy commercial foods and beverages tracks across the complementary feeding period in rural/peri‐urban Cambodia

Abstract: Consumption of unhealthy commercial foods and beverages (UCFB) is common among infants and young children living in low-and middle-income countries. Such foods can displace other nutritious foods, however, there is limited evidence on how this consumption tracks across time. This study assessed and tracked UCFB consumption of children living in rural/peri-urban Cambodia during the complementary feeding period, identified UCFB consumption patterns of these children, and explored the association between UCFB con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Finally, similar to reports in Cambodia [ 30 , 31 ], high consumption of unhealthy ‘Snacks and Soft Drinks’ among children was observed in rural Lao. Over half of children aged 6–23 months were found to partake in such consumption, with a significant increase noted among children aged 24–59 months, ranging from 50.4% to 71.2%.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, similar to reports in Cambodia [ 30 , 31 ], high consumption of unhealthy ‘Snacks and Soft Drinks’ among children was observed in rural Lao. Over half of children aged 6–23 months were found to partake in such consumption, with a significant increase noted among children aged 24–59 months, ranging from 50.4% to 71.2%.…”
Section: Discussionsupporting
confidence: 87%
“…These foods have the potential to normalize consumption of packaged, highly processed snack foods early in life and could result in continued, adverse snacking habits throughout childhood (World Health Organization, 2019 ). The consumption of unhealthy sweet/salty food products has been shown to persist across the complementary feeding period in HIC and LMIC settings (Hinnouho et al, 2023 ; Rose et al, 2017 ), and has been associated with reduced nutrient intakes (Webb et al, 2006 ), poorer dietary adequacy (Pries, Rehman, et al, 2019 ) and an increased risk of overweight later in childhood (Rose et al, 2017 ). A study among children 9–15 months of age in Australia reported that CPCF finger foods/snacks were consumed with the same frequency as other snack food products aimed at older child/adult populations (Moore et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is a lack of current evidence on CPCF consumption among young children in urban Cambodia, it is likely that consumption of these products has risen over the last decade, given that even peri‐urban areas are seeing an increase in commercial food consumption. A recent study found high consumption of unhealthy commercial food and beverages in peri‐urban Cambodia: 97.4% of young children at 15–19 months of age had consumed such products in the previous week (Hinnouho et al, 2023 ). Inadequate intakes of calcium among infants and young children in Cambodia has led to recommendations for the use of fortified foods to achieve optimal complementary feeding (Gibbs et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%